THE EFFECT OF PHYSICAL WORK ENVIRONMENT AND WORK DISPLINE ON EMPLOYEE PERFORMANCE AT PT. IVARO VENTURA SOUTH TANGERANG - Asridah Warni Tanjung; Ading Sunarto (International Journal of Multidisciplinary Research and Literature, 2023)
The purpose of this study was to determine the effect of the influence of the physical work environment and work discipline on the performance of employees of PT. Ivaro Ventura Ciputat either partially or simultaneously. the method used is quantitative. sampling technique using saturated sampling and obtained samples in this study amounted to 63 respondents. data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing, the results of this study are the regression equation Y = 4.471 + 0.585X1 + 0.312X2, the value of the correlation coefficient or the level of influence between The independent variable with the dependent variable was obtained at 0.792, which means that it has a strong relationship. the value of the coefficient of determination or contribution of influence simultaneously is 0.62.8 or 62.8% while the remaining 37.2% is influenced by other factors. hypothesis testing obtained F arithmetic > Ftable or (50.627 > 2.760). thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant effect of the physical work environment and work discipline on employee performance